Effects of Umbilical Cord Management Strategies on Stem Cell Transfusion, Delivery Room Adaptation, and Cerebral Oxygenation in Term and Late Preterm Infants - Okulu, Emel; Haskologlu, Sule; Guloglu, Deniz; Kostekci, Ezgi; Erdeve, Omer; Atasay, Begum; Koc, Acar; Soylemez, Feride; Dogu, Figen; Ikinciogullari, Aydan; Arsan, Saadet (Frontiers in Pediatrics, 2022)
Background: Umbilical cord blood contains a high concentration of stem cells. There isn’t any published study evaluating the amount of stem cells that have potential to be transferred to the infant through placental transfusion methods as delayed cord clamping (DCC) and umbilical cord milking (UCM). The aim of this study is to measure the concentrations of endothelial progenitor cell (EPC) and CD34+hematopoietic stem cell (HSC) in placental residual blood volume (PRBV), and evaluate the delivery room adaptation and cerebral oxygenation of these infants. Methods: Infants ≥36 gestational weeks were randomized to receive DCC (120 seconds) or UCM or immediate cord clamping (ICC). EPC and CD34+HSC were measured by flow cytometry from the cord blood. PRBV was collected in the setup. The cord blood gas analysis and complete blood count were performed. The heart rate (HR), oxygen saturation (SpO2), and cerebral regional oxygen saturation (crSO2) were recorded. Results: A total of 103 infants were evaluated. The amount of PRBV (as mL and mL/kg) was higher in ICC group (p<0.001). The number of EPCs in the PRBV content (both mL and mL/kg) were the highest in ICC group (p=0.002 and p=0.001, respectively). The number of CD34+ HSCs in PRBV content (mL and mL/kg) was similar in all groups, but non-significantly higher in ICC group. The APGAR scores at the 1st and 5th minutes were lower in ICC group (p<0.05). The mean crSO2 values were higher at the 3rd and 10th minutes in DCC group (p=0.042 and p=0.045, respectively). cFOE values were higher at the 3rd and 10th minutes in ICC group (p=0.011, and p<0.001, respectively). Conclusion: This study showed that placental transfusion methods as DCC and UCM provide both higher blood volume, more stem cells transfer to infant and better cerebral oxygenation in first minutes of life, whereas many lineages of stem cells is lost to placenta by ICC with higher residual blood volume. These cord management methods rather than ICC do not require any cost or technology, and may be a preemptive therapeutic source for diseases of neonatal period.